The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/aas.13068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined epidural anaesthesia on tumor‐infiltrating lymphocytes in lung adenocarcinoma: a prospective exploratory sub‐analysis

Abstract: For patients undergoing surgery for lung adenocarcinoma under general anesthesia, use of epidural anaesthesia increased CD8 T cells infiltration but decreased FOXP3 T cells accumulation in tumor tissues. Epidural anaesthesia may affect TILs in a manner that preserves immune function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…TILs could be affected by many factors. There is one study elucidated the epidural anaesthesia could preserves immune function and affect TILs [45]. According to another study, researchers found that tumor areas with CD4+ and CD8+ lymphocytes have a better prognosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…TILs could be affected by many factors. There is one study elucidated the epidural anaesthesia could preserves immune function and affect TILs [45]. According to another study, researchers found that tumor areas with CD4+ and CD8+ lymphocytes have a better prognosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative EA was reported to attenuate the immunosuppression by inhibiting the stress responses and/or alleviating the perioperative pain (58). Meanwhile, perioperative EA can improve the function of immunity via preserve and/or increase the numbers of immune cells and reduce the plasma concentrations of immune suppressive soluble factors (61)(62)(63)(64)(65).…”
Section: Perioperative Ea Attenuates Surgical Stress and Painmentioning
confidence: 99%
“…Regarding cellular mechanisms, a prospective randomized analysis of tumour-infiltrating lymphocytes in adenocarcinoma of the lung showed an increased CD8+ lymphocyte subset and a decrease in regulatory T cells in the histology of resected tumours in patients with a combined anaesthesia (general + epidural) in comparison to general anaesthesia alone [ 53 ] (Fig. 1 ).…”
Section: Pain Managementmentioning
confidence: 99%